«Scrivo, correggo e riscrivo». Su alcuni aspetti del dattiloscritto di "Se una notte d’inverno un viaggiatore" (ENTHYMEMA, 2020)
This paper focuses on some features of the of If on a Winter’s Night a Traveler typescript. Starting from a short description of the characteristics determining its complexity, some of Calvino’s reviews will be examined and will serve as the starting point for reflecting on the possible collocation of the fitness within the textual tradition.
Keywords: If on a Winter’s Night a Traveler; typescript; original reviews; textual criticism